Analysis Of Production Planning To Obtain Maximum Profit From “Es Kul-Kul” Sales Using The Simplex Method - Ambarsari, Ida Fitriana; Irawati, Santi; Hasanah, Nur; Astindari, Tri; Afifi, Basyiruddin (Universitas Wiralodra, 2025)
“Es Kul-Kul” production business located in a shop called the Muawanah Cooperative, is experiencing difficulty in maximizing profits due to changing consumer demand and challenges in determining the supply of raw materials needed. The owner continues to produce “Es Kul-Kul” based on the average daily consumer order, thereby sacrificing the efficiency of utilizing raw materials and capital. This study aims to analyze production planning to maximize profits from the sale of “Es Kul-Kul” at the Muawanah Cooperative UMKM using the simplex method. The research method employed in this study is a case study, with data analysis and processing conducted using linear programming, specifically the simplex method. The results of the study showed that the optimal production combination consisted of 50 banana-flavored skewers, and 100 strawberry-flavored skewers, with a total profit of IDR 800.000 per day. This approach has succeded in increasing production cost efficiency and optimizing profits, which is relevant for application to other UMKM. Possible further research is research based on optimization problems that occur in the surrounding environment with different methods and more detailed instruments to produce more accurate and realistic research.